The impact of dry-land sprint start training on the short track speed skating start - Haug, W. B.; Drinkwater, E. J.; Cicero, N. J.; Barthell, J. A.; Chapman, D. W. (The Journal of Strength and Conditioning Research, 2019)
This investigation sought to determine the effects of dry-land sprint start training on short track speed skating (STSS) start performance. Nine highly trained short track athletes completed a control period of normal STSS training followed by a 4-week training intervention. Before and after the control and intervention periods, athletes performed 3 electronically timed dry-land and on-ice 14.43 m maximal sprint start efforts. The intervention consisted of 2 sprint sessions per week consisting of 9 electronically timed 14.43 m dry-land sprint starts in addition to normal STSS training. The control period resulted in no substantial change in on-ice start performance (mean d: -0.01 seconds, 95% confidence limit [CL]: -0.08 to 0.05 seconds; effect size [ES]: -0.05; trivial); however, a small change was observed in dry-land start performance (mean d: -0.07 seconds, 95% CL: -0.13 to -0.02 seconds; ES: -0.49). After brief specific dry-land sprint start training, a small improvement was observed in both on-ice (Mean d: -0.07 seconds, 95% CL: -0.13 to -0.01 seconds; ES: -0.33) and dry-land (Mean d: -0.04 seconds, 95% CL: -0.09 to 0.00 seconds; ES: -0.29) start performance. This investigation suggests that STSS start performance can be improved through a brief dry-land sprint start training program.